Enhancing elementary student’s numeracy skills through ethnomathematics-based learning: An analysis of minimum competency assessment results - Larasati, Izah; Pramasdyahsari, Agnita Siska; Harun, Lukman (Universitas Papua, 2025)
The persistent issue of low numeracy skills among elementary school students remains a critical challenge in mathematics education, particularly in contexts where conventional pedagogical approaches fail to connect mathematical concepts to students' lived experiences. Despite growing advocacy for culturally responsive teaching, limited empirical evidence exists regarding the integration of ethnomathematics within the Mathematics Contextual Approach (MCA) to address this gap. This study introduces a novel instructional strategy by embedding ethnomathematics-based learning into the MCA framework to enhance numeracy skills through culturally and contextually relevant mathematics instruction. The research aimed to examine the effectiveness of this integrated approach at SD Negeri 04 Temuireng using a quasi-experimental one-group pretest-posttest design involving 30 fifth-grade students. Data were collected through test and non-test instruments, with numeracy assessments based on the government-developed MCA test. Statistical analysis utilizing a paired sample t-test revealed a significant improvement in students’ numeracy skills, with mean scores increasing from 27.83 (pretest) to 56.17 (posttest), a Sig. (2-tailed) value of 0.000, and an average N-gain of 0.3696. These findings underscore the potential of ethnomathematics-based learning to foster a deeper understanding of mathematical concepts by leveraging students' cultural knowledge and real-world experiences. The results contribute to the discourse on curriculum innovation by highlighting the role of ethnomathematics in developing meaningful, contextualized, and equitable mathematics education practices.